The impact of chorionicity and assisted reproductive therapies in obstetric and neonatal outcomes. (18th April 2022) - Ferraz Liz, Catarina; Domingues, Sara; Guedes, Ana; Lopes, Luísa
Abstract: Objective: Multiple gestations' incidence have raised worldwide in the last years, much due to assisted reproductive therapies (ART). The goal of this study was to analyze obstetric and neonatal outcomes of twin pregnancies in a level 3 maternity. Methods: A retrospective study including all twins born in a period of 12 years in a level 3 maternity was conducted. Analysis comparing spontaneous monochorionic and dichorionic twins and spontaneous and ART dichorionic twins were performed. A p value < .05 was considered statistically significant. Results: The sample included 1783 newborns from 875 mothers. Mean maternal age was 31 years, with 616 spontaneous pregnancies and 259 through ART. Prematurity occurred in 77%. Congenital malformations were found in 6%, and the mortality rate was 3%. Monochorionic twins had higher prematurity (79% vs 72%) and very low birthweight (VLBW) rate (19% vs 14%). Congenital anomalies (9% vs 6%), Respiratory Distress Syndrome (23% vs 18%), patent ductus arteriosus (7% vs 4%), anemia (11% vs 5%), periventricular hemorrhage (5% vs 3%), mechanical ventilation (16% vs 10%) and mortality (4% vs 2%) were higher in monochorionic twins. Although congenital malformations were more frequent in the ART group, the difference was not statistically significant. The effect of ART in neonatal and obstetric outcomes was related to maternal age. Conclusion: Monochorionic pregnancies were associated with worst obstetric and neonatal outcomes. Although congenital malformations were more frequent in the ART group, the difference was not statistically significant. Most obstetric and neonatal complications were related to advanced maternal age.